2016
DOI: 10.1071/rd14199
|View full text |Cite
|
Sign up to set email alerts
|

Maternal treatment with fluoxetine promotes testicular alteration in male rat pups

Abstract: Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRI) antidepressant commonly prescribed during pregnancy and lactation. Pre- and post-partum depression, as well as SSRI treatment during these periods, may change maternal care, interfering with offspring development. Moreover, it is known that SSRIs may alter testes structure and function in offspring. The present study investigated the effects of maternal FLX exposure on maternal behaviour and testes function in offspring. Female Wistar rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
5
0
2
Order By: Relevance
“…Another study also confirmed the genotoxic Histomorphometric analyses in the testicular tissue showed significant decrease in epithelial height and diameter of SNTs in mice receiving CeO 2 NPs comparing the control group. These alterations could be related to the decrease in the number of Sertoli cells because there is a direct correlation between the number of Sertoli cells and epithelial height and diameter of SNTs (36,37). In the present study, the number of Sertoli cells was not evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Another study also confirmed the genotoxic Histomorphometric analyses in the testicular tissue showed significant decrease in epithelial height and diameter of SNTs in mice receiving CeO 2 NPs comparing the control group. These alterations could be related to the decrease in the number of Sertoli cells because there is a direct correlation between the number of Sertoli cells and epithelial height and diameter of SNTs (36,37). In the present study, the number of Sertoli cells was not evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Although an increase in kidney weight was observed, which could be associated with damage to this organ, Perinatal exposure to SSRI can increase 5-HT availability in the testes and epididymis of offspring during the critical period of development, resulting in downregulation of 5-HT receptors in testicular and epididymal cells. These modifications during the development of the testis and epididymis can cause persistent changes in sperm quality and/or quantity (Ramos et al, 2016). Studies have revealed that a local serotonergic system is found in rat caput epididymis including the expression of 5-HT biosynthetic enzymes, 5-HT receptors, and serotonin transporters (Jiménez-Trejo et al, 2007), and disturbances in this serotonergic system have been associated with changes in sperm count and motility as well as ejaculatory alterations (Gonzales et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the drugs that enhance or inhibit serotonin activity may have implications on reproduction. The use of antidepressants such as selective serotonin reuptake inhibitors (SSRI) induce negative reproductive effects in adult men [ 59 ], in woman during pregnancy [ 60 ], and male exposed in utero [ 61 ]. SSRI and are widely prescribed for children and adolescents, although data regarding their safety are limited [ 62 ].…”
Section: Discussionmentioning
confidence: 99%